2000
DOI: 10.1021/jf990976z
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Shear Rheology of Aged and Heat-Treated β-Lactoglobulin Films:  Displacement by Nonionic Surfactant

Abstract: Interfacial shear rheology of adsorbed beta-lactoglobulin films (bulk protein concentration 10(-)(3) wt %) has been studied over the temperature range 20-90 degrees C using a two-dimensional Couette-type viscometer. Effects of the type of interface (air-water, triolein-water, and n-dodecane-water), the pH (2.0, 5.6, 6.0, 7.0, and 9.0), and the extent of the heat treatment have been assessed via measurements of changes in the apparent interfacial shear viscosity and elasticity before and after the addition of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
108
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 30 publications
11
108
0
1
Order By: Relevance
“…However, at higher temperatures (90 C, as in our case), whey proteins become fully unfolded and are able to rearrange effectively all nonpolar amino acids towards the oil phase, thus reducing the tendency for aggregation. Hence, it might be a possibility that the heat treatment promoted WPM particle-particle fusion on the surface of the droplets rather than inter-droplet interactions as reported in previous literatures 31,39,40 . The TEM images ( Figure 3A1 and Figure 3A2) show clearly that WPM particles were adsorbed on the surface of the emulsion droplets.…”
Section: Characteristics Of Emulsions Stabilized By Wpm Particlesmentioning
confidence: 82%
See 1 more Smart Citation
“…However, at higher temperatures (90 C, as in our case), whey proteins become fully unfolded and are able to rearrange effectively all nonpolar amino acids towards the oil phase, thus reducing the tendency for aggregation. Hence, it might be a possibility that the heat treatment promoted WPM particle-particle fusion on the surface of the droplets rather than inter-droplet interactions as reported in previous literatures 31,39,40 . The TEM images ( Figure 3A1 and Figure 3A2) show clearly that WPM particles were adsorbed on the surface of the emulsion droplets.…”
Section: Characteristics Of Emulsions Stabilized By Wpm Particlesmentioning
confidence: 82%
“…This is unlike the behaviour of typical whey protein-stabilized emulsions which shows detectable amount of oiling off during gastric digestion, possibly due to the inability of fragmented peptides generated to protect the oil droplets against droplet coalescence 37 . Thus both WPM particles and HT WPM fused particles offered a good protection to oil droplets against coalescence during gastric digestion as compared to typical protein-stabilized interfaces 40 . Figure 6 describes the interfacial composition of the gastric digested interfaces, in terms of bovine serum albumin (BSA) (66 kDa), -Lactalbumin ( -La) (14 kDa), -Lactoglobulin dimers ( -Lg dimers) (36 kDa), -lactoglobulin monomers ( -lg) (18 kDa) as determined by SDS-PAGE.…”
mentioning
confidence: 92%
“…5B-1) will not be sufficient to form a continuous network that would lead to an increase of surface shear elasticity. Rapid formation of higher aggregates could be induced, however, but only by In this respect, the work by Roth et al [15] provides interesting observations. In this work the surface shear viscosity of adsorbed h-lactoglobulin was measured during a 24 h period.…”
Section: Discussionmentioning
confidence: 99%
“…Two different processes can be the cause of this transition. Firstly, the repulsion between adsorbed particles can be overcome by thermal treatment as described by Roth et al [15] and Hellebust at al. [52].…”
Section: Discussionmentioning
confidence: 99%
“…This is beneficial, because it is known that a number of proteins unfold irreversibly when exposed to the water/air interface. Roth et al (2000) [33] have shown that the detergent polysorbate 20 is able to displace β-lactoglobulin molecules from the water/air interface, and as a consequence, the protein concentration at the water/air interface is strongly reduced.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%